The influence of oxidative stress and autophagy cross regulation on pregnancy outcome - de Andrade Ramos, Bruna Ribeiro [UNESP]; Witkin, Steven S. [UNESP] (Elsevier, 2016)
The generation of reactive oxygen species (ROS), a byproduct of aerobic energy metabolism, is maintained at physiological levels by the activity of antioxidant components. Insufficiently opposed ROS results in oxidative stress characterized by altered mitochondrial function, decreased protein activity, damage to nucleic acids, and induction of apoptosis. Elevated levels of inadequately opposed ROS induce autophagy, a major intracellular pathway that sequesters and removes damaged macromolecules and organelles. In early pregnancy, autophagy induction preserves trophoblast function in the low oxygen and nutrient placental environment. Inadequate regulation of the ROS-autophagy axis leads to abnormal autophagy activity and contributes to the development of preeclampsia and intrauterine growth restriction. ROS-autophagy interactions are altered at the end of gestation and participate in the initiation of parturition at term. The induction of high levels of ROS coupled with a failure to induce a corresponding increase in autophagy results in the triggering of preterm labor and delivery.
Keywords: Autophagy; Intrauterine growth restriction; Oxidative stress; Preeclampsia; Pregnancy; Preterm birth